Accuracy and precision of dolphin group size estimates. Issue 1 (14th May 2018) - Gerrodette, Tim; Perryman, Wayne L.; Oedekoven, Cornelia S.
Abstract: Estimating the number of dolphins in a group is a challenging task. To assess the accuracy and precision of dolphin group size estimates, observer estimates were compared to counts from large‐format vertical aerial photographs. During 11 research cruises, a total of 2, 435 size estimates of 434 groups were made by 59 observers. Observer estimates were modeled as a function of the photo count in a hierarchical Bayesian framework. Accuracy varied widely among observers, and somewhat less widely among dolphin species. Most observers tended to underestimate, and the tendency increased with group size. Groups of 25, 50, 100, and 500 were underestimated by <1%, 16%, 27%, and 47%, respectively, on average. Precision of group size estimates was low, and estimates were highly variable among observers for the same group. Predicted true group size, given an observer estimate, was larger than the observer estimate for groups of more than about 25 dolphins. Predicted group size had low precision, with coefficients of variation ranging from 0.7 to 1.9. Studies which depend on group size estimates will be improved if the tendency to underestimate group size and the high uncertainty of group size estimates are included in the analysis.